Distributing Reflexivity through Co-laborative Ethnography. (February 2021) - Bieler, Patrick; Bister, Milena D.; Hauer, Janine; Klausner, Martina; Niewöhner, Jörg; Schmid, Christine; von Peter, Sebastian
In ethnographic research and analysis, reflexivity is vital to achieving constant coordination between field and concept work. However, it has been conceptualized predominantly as an ethnographer's individual mental capacity. In this article, we draw on ten years of experience in conducting research together with partners from social psychiatry and mental health care across different research projects. We unfold three modes of achieving reflexivity co-laboratively: contrasting and discussing disciplinary concepts in interdisciplinary working groups and feedback workshops; joint data interpretation and writing; and participating in political agenda setting. Engaging these modes reveals reflexivity as a distributed process able to strengthen the ethnographer's interpretative authority, and also able to constantly push the conceptual boundaries of the participating disciplines and professions.